2016
DOI: 10.1097/pas.0000000000000675
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent NTRK1 Gene Fusions Define a Novel Subset of Locally Aggressive Lipofibromatosis-like Neural Tumors

Abstract: The family of pediatric fibroblastic and myofibroblastic proliferations encompasses a wide spectrum of pathologic entities with overlapping morphologies and ill-defined genetic abnormalities. Among the superficial lesions, lipofibromatosis (LPF), composed of an admixture of adipose tissue and fibroblastic elements, in the past has been variously classified as infantile fibromatosis or fibrous hamartoma of infancy. In this regard, we have recently encountered a group of superficial soft tissue tumors occurring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
298
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 198 publications
(312 citation statements)
references
References 32 publications
9
298
0
5
Order By: Relevance
“…7, 8 One additional tumor considered in the differential diagnosis was the recently described S100-positive lipofibromatosis-like neural tumor, which can occur in young children, including infants. 5 Similar to our case, these lesions may show areas of increased cellularity, scattered mitotic activity, and an infiltrative growth within adjacent adipose tissue. However, they also show CD34 and NTRK1 reactivity and NTRK1 gene rearrangements.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…7, 8 One additional tumor considered in the differential diagnosis was the recently described S100-positive lipofibromatosis-like neural tumor, which can occur in young children, including infants. 5 Similar to our case, these lesions may show areas of increased cellularity, scattered mitotic activity, and an infiltrative growth within adjacent adipose tissue. However, they also show CD34 and NTRK1 reactivity and NTRK1 gene rearrangements.…”
Section: Discussionsupporting
confidence: 80%
“…Lastly, the most recent example is the lipofibromatosis-like neural tumor with recurrent NTRK1 -related fusions, in which the neural phenotype was defined based on its consistent S100 protein reactivity, but similarly lacking SOX10 positivity. 5 The significance of S100 positivity alone remains elusive and additional studies are required to establish if this finding is indeed related to neuroectodermal differentiation. Furthermore, these examples illustrate that immunohistochemical results taken out of context might be misleading in the setting of fusion-positive mesenchymal tumors, where there is often no good correlation between immunoprofile and line of differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their cases showed consistently high mitotic activity, ranging from 12–17 MF/ 10 HPFs. It remains unclear if these NTRK1 -rearraranged atypical/malignant myofibroblastic tumors have any relationship to our cohort of cellular myofibroblastic lesions, since all 20 cases of myofibromas/myopericytomas, spanning classic, cellular and malignant examples, from our files lacked NTRK1 genetic abnormalities 16 . We believe that the cases described recently by Linos and colleagues 17 , as ‘myofibroma with atypical features’, based on increased cellularity, infiltrative borders and increased mitotic activity (but not increased pleomorphism), resemble closely our cohort and may represent SRF -positive cellular variants of myofibroma or myoepricytoma as described here.…”
Section: Discussionmentioning
confidence: 99%
“…No staining with antibodies against desmin, GFAP, STAT6, HMB45, Melan-A, and SOX10 was reported. Agaram et al [80] reported a TPR-NTRK1 or TPM3-NTRK1 gene fusion in 71% of cases. Furthermore, the performed NTRK1 immunostaining was positive only in NTRK1-rearranged S100-positive LPF-NT but negative in classic LPF.…”
Section: Recently Described New Entities Of the Soft Tissuementioning
confidence: 99%